Drimane Sesquiterpene Alcohols with Activity against Candida Yeast Obtained by Biotransformation with Cladosporium antarcticum - Paz, Cristian (International Journal of Molecular Sciences, 2024)
This research was funded by the Chilean Institute INACH with the grant RT33-18 and by ANID Chile under Fondecyt 1220831 granted to C.P. MALDI-TOF MS analyses were partially developed using an equipment funded by CONICYT/Chile through the project Fondequip EQM160054 2016. Esta investigación fue financiada por el Instituto Chileno INACH con la beca RT33-18 y por ANID Chile bajo el Fondecyt 1220831 otorgado a C.P. Los análisis MALDI-TOF MS se desarrollaron parcialmente utilizando un equipo financiado por CONICYT/Chile a través del proyecto Fondequip EQM160054 2016. Fungal biotransformation is an attractive synthetic strategy to produce highly specific compounds with chemical functionality in regions of the carbon skeleton that are not easily activated by conventional organic chemistry methods. In this work, Cladosporium antarcticum isolated from sediments of Glacier Collins in Antarctica was used to obtain novel drimane sesquiterpenoids alcohols with activity against Candida yeast from drimendiol and epidrimendiol. These compounds were produced by the high-yield reduction of polygodial and isotadeonal with NaBH4 in methanol. Cladosporium antarcticum produced two major products from drimendiol, identified as 9 alpha-hydroxydrimendiol (1, 41.4 mg, 19.4% yield) and 3 beta-hydroxydrimendiol (2, 74.8 mg, 35% yield), whereas the biotransformation of epidrimendiol yielded only one product, 9 beta-hydroxyepidrimendiol (3, 86.6 mg, 41.6% yield). The products were purified by column chromatography and their structure elucidated by NMR and MS. The antifungal activity of compounds 1-3 was analyzed against Candida albicans, C. krusei and C. parapsilosis, showing that compound 2 has a MIC lower than 15 mu g/mL against the three-pathogenic yeast. In silico studies suggest that a possible mechanism of action for the novel compounds is the inhibition of the enzyme lanosterol 14 alpha-demethylase, affecting the ergosterol synthesis.